"\\frac{1}{x^2}\\frac{\u2202^2z}{\u2202x^2} - \\frac{1}{x^3}\\frac{\u2202z}{\u2202x}= \\frac{1}{y^2}\\frac{\u2202^2z}{\u2202y^2}- \\frac{1}{y^3}\\frac{\u2202z}{\u2202y}"
Putting, "X = \\frac{1}{2}x^2, Y = \\frac{1}{2}y^2"
then, "xdx = dX, ydy = dY"
so,
"\\frac{\\partial z}{\\partial X} =\\frac{\\partial z}{\\partial x}\\frac{\\partial x}{\\partial X} = \\frac{1}{x}\\frac{\\partial z}{\\partial x}"
and "\\frac{\\partial^2 z}{\\partial X^2} = \\frac{\\partial }{\\partial X}(\\frac{\\partial z}{\\partial X}) = \\frac{\\partial }{\\partial x}(\\frac{1 }{ x}\\frac{\\partial z}{\\partial x})\\frac{\\partial x}{\\partial X}"
"= -\\frac{1}{x^3}\\frac{\\partial z}{\\partial x} + \\frac{1}{x^2}\\frac{\\partial^2 z}{\\partial x^2}"
Similarly, "\\frac{\\partial^2 z}{\\partial Y^2}= -\\frac{1}{y^3}\\frac{\\partial z}{\\partial y} + \\frac{1}{y^2}\\frac{\\partial^2 z}{\\partial y^2}"
This transformation will lead the equation,
"\\frac{\\partial^2 z}{\\partial X^2} - \\frac{\\partial^2 z}{\\partial Y^2} = 0"
"(D^2-D^{'2})z = 0" where
"D^2 = \\frac{\\partial^2 }{\\partial X^2}, D^{'2} = \\frac{\\partial^2 }{\\partial Y^2}""(D +D')(D -D')z = 0"
solution of the equation,
"z = \\phi_1(Y-X)+\\phi_2(Y+X)"
"z = f_1(y^2-x^2)\n+ f_2(y^2+x^2)"
Comments
Leave a comment